2016
DOI: 10.1007/8904_2016_561
|View full text |Cite
|
Sign up to set email alerts
|

Management of an LCHADD Patient During Pregnancy and High Intensity Exercise

Abstract: In this report we describe a female Long-Chain 3-Hydroxyacyl-CoA Dehydrogenase Deficiency (LCHADD) patient who suffered from severe exercise intolerance. At age 34, the patient became pregnant for the first time. After an uneventful first 32 weeks of pregnancy she developed sinus tachycardia (resting heart rate 120-134 bpm) and lactate and creatinine kinase levels increased (3.3 mmol/L and 264 U/L, respectively). Increasing MCT supplementation (dose and frequency of administration) lowered heart rate and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Nor do they improve the lethargy and exercise intolerance commonly experienced among patients with defects in FAOD. 1 As a result, patients often have a more sedentary lifestyle than similarly aged normal counterparts. 12 A relatively low protein intake could compound the loss of LBM that accompanies disuse atrophy, and aging sarcopenia contributing to the lethargy and exercise intolerance that patients with FAOD already experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nor do they improve the lethargy and exercise intolerance commonly experienced among patients with defects in FAOD. 1 As a result, patients often have a more sedentary lifestyle than similarly aged normal counterparts. 12 A relatively low protein intake could compound the loss of LBM that accompanies disuse atrophy, and aging sarcopenia contributing to the lethargy and exercise intolerance that patients with FAOD already experience.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with LC-FAOD report muscle pain and lethargy with exercise and can become increasingly more sedentary over time. 1,31 Disuse muscle atrophy would be expected to affect both LBM and the ability to maintain activities of daily living. We did not measure participant activity in this study, so we cannot report whether these differences in LBM between the diet groups was able to close the "activity gap" in TEE of participants with LC-FAODs compared to normal controls that we have previously hypothesized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restricting the consumption of specific fatty acids has been trialled in several FAO disorders [112][113][114], aiming to reduce the build-up of potentially toxic intermediates [115]. In a similar fashion, ketogenic (keto) diets are designed to decrease the amount of long-chain fatty acids, reducing the burden on medium-chain and short-chain acyl-CoA dehydrogenases to limit the build-up of fatty acyl-CoA intermediates [116,117].…”
Section: Treatment Of Mitochondrial Disease and Echs1dmentioning
confidence: 99%
“…In addition to these dietary regimens, many FAOD patients are given carnitine supplementation to prevent secondary carnitine deficiency due to acylcarnitine secretion. While a few studies have demonstrated positive effects of MCT [78-80] there is most certainly a need for better therapeutic options. Unfortunately, a drug known as bezafibrate that showed promise in cell culture studies [81] was recently assessed in clinical trials and found to have no efficacy in patients with long-chain FAOD [82, 83].…”
Section: Advances In Therapymentioning
confidence: 99%